2002
DOI: 10.3317/jraas.2002.004
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress increases the expression of the angiotensin-II receptor type 1 in mouse peritoneal macrophages

Abstract: Angiotensin II (Ang II) has been shown to accelerate atherogenesis, and the cellular Ang II type 1 (AT 1 ) -receptor mediates most of Ang II-induced proatherogenic effects. In this study we have examined the effect of macrophage oxidative stress on cellular AT 1 -receptor expression.Mouse peritoneal macrophages (MPM) from apolipoprotein-E deficient (E 0 ) mice at increasing ages (1-6 months) demonstrated an age-dependent increase in cellular lipid-peroxides (PD) content. In parallel, the AT 1 -receptor mRNA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…37 The proatherogenic effects of AII and the anti-atherogenic effects of ACEI and ARB have been linked to modulation of macrophage functions, including chemotaxis, intimal recruitment, inflammation, neovascularization, and proteolysis. 3, 4, 8, 9 AII can modulate macrophage-specific functions, as supported by observations that monocyte/macrophages express components of the angiotensin system, including the aongiotensin II type 1 receptor (AT1), and that cellular exposure to AII promotes lipid accumulation, migration and cytokine production. 4, 8, 9 Nonetheless, the specific contribution in vivo of the macrophage AT1 receptor to atherogenesis has been controversial, ranging from little influence observed in some studies 10 to significant proatherogenic effects reported by others, especially in the setting of infusion of exogenous AII.…”
Section: Introductionmentioning
confidence: 87%
“…37 The proatherogenic effects of AII and the anti-atherogenic effects of ACEI and ARB have been linked to modulation of macrophage functions, including chemotaxis, intimal recruitment, inflammation, neovascularization, and proteolysis. 3, 4, 8, 9 AII can modulate macrophage-specific functions, as supported by observations that monocyte/macrophages express components of the angiotensin system, including the aongiotensin II type 1 receptor (AT1), and that cellular exposure to AII promotes lipid accumulation, migration and cytokine production. 4, 8, 9 Nonetheless, the specific contribution in vivo of the macrophage AT1 receptor to atherogenesis has been controversial, ranging from little influence observed in some studies 10 to significant proatherogenic effects reported by others, especially in the setting of infusion of exogenous AII.…”
Section: Introductionmentioning
confidence: 87%
“…Oxidative stress increases the expression of the AT1 receptor in monocytes/macrophages, which can enhance macrophage formation [66]. Moreover, ANGII may induce cellular responses through free radical generation [41], particularly through NAD(P)H complex [67], which mediates the activation of protein kinase B and JAK/STAT signaling.…”
Section: The Angiotensin System and Monocytes/ Macrophagesmentioning
confidence: 99%
“…The effects of oxidative stress on AT 1 receptor expression were also studied in macrophages, since Ang II is a proatherogenic molecule and both oxidative stress and AT 1 receptor expression are increased in hypercholesterolaemia [145][146][147]. In mouse peritoneal macrophages (MPMs) harvested from the E 0 mice, an animal model of severe hypercholesterolemia and atherosclerosis caused by apolipoprotein E deficiency, there was an age-dependent increase in lipid peroxide content accompanied by an age-dependent increase in the AT 1 receptor mRNA and protein expression [146]. MPMs obtained from 3.5 months old E 0 mice treated for 6 weeks with the potent antioxidant vitamin E had lower lipid peroxides concentration and reduced AT 1 receptor mRNA expression, compared to MPMs harvested from untreated E 0 mice [146].…”
Section: Ros and Ang Receptorsmentioning
confidence: 99%
“…In mouse peritoneal macrophages (MPMs) harvested from the E 0 mice, an animal model of severe hypercholesterolemia and atherosclerosis caused by apolipoprotein E deficiency, there was an age-dependent increase in lipid peroxide content accompanied by an age-dependent increase in the AT 1 receptor mRNA and protein expression [146]. MPMs obtained from 3.5 months old E 0 mice treated for 6 weeks with the potent antioxidant vitamin E had lower lipid peroxides concentration and reduced AT 1 receptor mRNA expression, compared to MPMs harvested from untreated E 0 mice [146]. To further demonstrate the role of oxidative stress in the regulation of macrophage AT 1 receptor, the GSH content was manipulated by the supplementation for 5 weeks with BSO or with L-2-oxothiazolidine-4-carboxylic acid (OTC), a precursor of GSH synthesis.…”
Section: Ros and Ang Receptorsmentioning
confidence: 99%